Supervision in continuous teacher training - Carlos, Ana Paula (2017)
The concept of Supervision is not new, however, in the XXI century, has been reframed and gained a more relevant status in Portugal, because it operates in a changing context of the exercise of the teaching profession, emerging associated with a new paradigm of teachers’ intervention and action. With regard, continuing education is assumed as a determining factor, and therefore the present study searched for i) evidence of implementation of supervising nature of supervision practices and iii) perceptions/opinions of those involved in the CFAEs, in order to establish the concept of supervision of its stakeholders. We followed a multiple case study design, selected and characterized five CFAEs geographically dispersed in the Portuguese mainland (North, Centre, Lisbon and South), we developed instruments for opinion collection, with a sample of directors, trainers and trainees with a mixed methodology: qualitative through interview with the directors of the CFAE’s and quantitative (the predominant approach) through a questionnaire applied to trainees and trainers (who do not accumulate those two functions in the period of analysis). Results of both the interviews and the questionnaires were presented by category. The relevance of pedagogical supervision in order to present a recognized and respected praxis is therefore assumed, with the purpose of making it essential to the efficient and effective balance of the Education and Training system(s) in Portugal.